2005
DOI: 10.1111/j.1366-9516.2005.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

A pleasing consequence of Norway rat eradication: two shrew species recover

Abstract: Four to 10 years after the successful eradication of the Norway rat ( Rattus norvegicus ) from three islands of the Sept-Îles Archipelago and one in the Molène Archipelago (Brittany, France), the abundance index of the lesser white-toothed shrew ( Crocidura suaveolens ) increased by factors of 7-25, depending on the island and the year. Moreover, in the same region, the abundance index of the greater white-toothed shrew ( Crocidura russula ) on Tomé Island increased by factors of 9 and 17, one and two years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 8 publications
2
18
1
Order By: Relevance
“…Questing tick distribution in the environment is the result of their location when they detached from hosts, of their survival capability, questing activity and lateral movements, although I. ricinus ticks are considered to move no more than a few meters (Gray 1985;Carroll and Schmidtmann 1996). The simultaneous observation of small mammals on the study sites led to an index of abundance rather small, but in accordance with the normal Xuctuation found in France (Le Louarn and Quéré 2003;Pascal et al 2005). Only one small mammal species, A. sylvaticus, used all three habitat types, woodland, hedgerow and grassland.…”
Section: Discussionsupporting
confidence: 67%
“…Questing tick distribution in the environment is the result of their location when they detached from hosts, of their survival capability, questing activity and lateral movements, although I. ricinus ticks are considered to move no more than a few meters (Gray 1985;Carroll and Schmidtmann 1996). The simultaneous observation of small mammals on the study sites led to an index of abundance rather small, but in accordance with the normal Xuctuation found in France (Le Louarn and Quéré 2003;Pascal et al 2005). Only one small mammal species, A. sylvaticus, used all three habitat types, woodland, hedgerow and grassland.…”
Section: Discussionsupporting
confidence: 67%
“…Pre-to post-eradication changes in abundance provided evidence of R. rattus repression of the two Western Australian marsupials Bettongia lesueur (Boodie Island) and I. a. barrowensis (Middle Island) as well as the Anacapa deer mouse Peromyscus maniculatus anacapae of Anacapa Island, Southern California (Morris 2002;Gellerman 2007). Post-eradication expansion across entire islands strongly suggested that two species (C. suaveolens and B. lesueur) had been locally displaced by introduced Rattus species (Morris 2002; Pascal et al 2005). The possibility that C. suaveolens was actually absent from Les Mottes Islets (Brittany, France) and has recolonised from a neighbouring island since the eradication of R. norvegicus also supports this theory (Pascal et al 2005).…”
Section: Introduced Rodent Impact On Extant Insular Small Mammals-'exmentioning
confidence: 83%
“…An increase in the abundance of C. suaveolens followed the eradication of R. norvegicus on four islands; three in the SeptÎles Archipelago and one in the Molène Archipelago (Brittany, France). Furthermore, the response to eradication can be separated from any effects of environmental variation by comparison to the population dynamics on rat-free Béniguet Island (Molène Archipelago) illustrating the value of comparative 'control' data (Pascal et al 2005). The repression of the dusky shrew S. monticolus was also lifted by the eradication of R. norvegicus on Langara Island, British Columbia (Canada).…”
Section: Introduced Rodent Impact On Extant Insular Small Mammals-'exmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible way to investigate these processes is by identifying spatio-temporal associations between species recolonization and decrease in human pressure, due to socioeconomic changes or conservation policies. At present, some studies document recolonizations by threatened species (Swenson et al 1998;Pacheco and McGregor 2004;Davies et al 2005;Pascal et al 2005), however, to our knowledge, no study has attempted to make a quantitative large-scale analysis of human impacts on species distribution at different times to investigate recolonization processes.…”
Section: Introductionmentioning
confidence: 94%